Climate and environmental change along the East Coast of South Africa: perspectives from a local marine resource- dependent community and scientific researchers - Duba, Tania (Department of Environmental and Geographical Science, 2020)
Coastal areas are very susceptible to environmental problems such as sea-level rise, coastal flooding, increased frequency and intensity of extreme events, and changes in marine ecosystems that are arising from global climate change and variability. In the South African context, the Agulhas Current is important for its crucial role in regional climate and weather as well as the fishing livelihood of the coastal communities along the east coast of South Africa. Despite the efforts made to understand the Agulhas Current and the impacts of climate and environmental change, the shelf region remains poorly understood mostly due to the difficulties associated with observing and modelling such strong currents. The marine resource users in the fishing communities along the east coast of South Africa show long term dependence on the neighbouring ocean going back at least three generations. These communities provide long term, rich, detailed, and contextualized environmental knowledge from their daily interactions with the sea. This study seeks to investigate the local climate and environmental change knowledge of the fishers based on their own observations, perceptions, and experiences. The convergence/divergence of the marine resource user’s knowledge with the traditional scientific findings is explored using a broad, participatory methodology including desktop literature analysis, interviews and an adopted version of the Rapid Vulnerability Assessment (RVA). Results show that fishers in Tshani-Mankosi have observed changes in the rainfall, sea surface temperature and wind patterns in their community. According to the fishers, sea surface temperature and annual rainfall seem to have decreased while winds and rainfall related extreme events have increased. Similar observations were noticed in the scientific research at a larger spatial and temporal scale. Key differences and similarities between the two types of knowledge come from factors such as knowledge construction processes, scales, type of data output and parameters of interest. Finally, the study reveals opportunities and challenges of research collaboration between the community and scientific researchers.